2012
DOI: 10.1002/ps.2309
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of fungicides for the management of Botryosphaeria dieback diseases of grapevines

Abstract: This research has demonstrated that fungicides applied after winter pruning can protect vines from infection by conidia of three botryosphaeriaceous species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
30
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 15 publications
3
30
1
1
Order By: Relevance
“…seriata, N. australe and N. parvum (Bester and Fourie, 2005;Savocchia et al, 2005;Bester et al, 2007;Auger et al, 2010;Amponsah et al, 2012). Additionally, our results agree with a recently published report (Pitt et al, 2012) indicating that tebuconazole and myclobutanil are very effective at controlling the mycelial growth of D. seriata and N. parvum in vitro.…”
Section: Discussionsupporting
confidence: 91%
“…seriata, N. australe and N. parvum (Bester and Fourie, 2005;Savocchia et al, 2005;Bester et al, 2007;Auger et al, 2010;Amponsah et al, 2012). Additionally, our results agree with a recently published report (Pitt et al, 2012) indicating that tebuconazole and myclobutanil are very effective at controlling the mycelial growth of D. seriata and N. parvum in vitro.…”
Section: Discussionsupporting
confidence: 91%
“…Many different studies have been carried out to monitor pruning wound protection with chemical antifungals such as benomyl, carbendazim, fosetyl, tebuconazole, or thiophanate-methyl, among others (7,20,23,25,26,45), to cite only the latest. Some of these chemical fungicides have proven to be effective at different rates in the protection of pruning wounds.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, when Rolshausen et al (7) evaluated the efficacy of different fungicides in controlling both Petri disease pathogens and infections from several Botryosphaeriaceae species, they found that thiophanate-methyl was most effective. More recently, Amponsah et al (25) reported that 9 out of the 16 fungicides tested were effective in inhibiting the growth of several Botryosphaeriaceae species, reducing mycelial growth and/or conidial germination. Assays on potted and field grapevines showed various degrees of protection; flusilazole and carbendazim were the most effective.…”
mentioning
confidence: 99%
“…Therefore, based on the presented results OA medium could be recommended as a suitable for radial growth assays for D. applanata, despite the fact that PDA medium is one of the most commonly used culture media for in vitro fungicide sensitivity evaluation. [21][22][23][24] The results also showed that most of the D. applanata isolates collected at five different locations in western Serbia were sensitive to the fungicides tested. However, the EC 50 values differed depending on both fungicides and isolates.…”
Section: Discussionmentioning
confidence: 98%